2022
DOI: 10.1371/journal.pone.0272556
|View full text |Cite
|
Sign up to set email alerts
|

The association between fecal microbiota, age and endoparasitism in adult alpacas

Abstract: Endoparasitism is a major cause of morbidity and mortality in alpacas (Lama pacos), with growing emergence of anthelmintic resistance. The purpose of the study was to correlate nematode worm burden and selected host phenotypic characteristics, such as age and weight, with the composition of the intestinal microbiota of adult alpacas. Fecal samples were collected per rectum from 102 healthy adult (2.1–11.2 years) alpacas at 3 separate timepoints (pre- and post-treatment with 8.8 mg/kg oral Levamisole HCL, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This might be partially attributed to the distinct alpaca behaviour of establishing Since alpacas do not normally graze around these latrines when sufficient grazing is available, they may avoid acquiring a high level of infection. It is important to note that this is not always the case and that alpacas have been found to have higher FECs (> 300 epg) in some studies (Bedenice et al 2022); which might be attributed to the differences in the location of these latrines. It is not the scope of this study, but it will be interesting to investigate how this behaviour Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This might be partially attributed to the distinct alpaca behaviour of establishing Since alpacas do not normally graze around these latrines when sufficient grazing is available, they may avoid acquiring a high level of infection. It is important to note that this is not always the case and that alpacas have been found to have higher FECs (> 300 epg) in some studies (Bedenice et al 2022); which might be attributed to the differences in the location of these latrines. It is not the scope of this study, but it will be interesting to investigate how this behaviour Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Since alpacas do not normally graze around these latrines when su cient grazing is available, they may avoid acquiring a high level of infection. It is important to note that this is not always the case and alpacas have been found to have 300 + FECs in some studies (Bedenice et al, 2022), which can potentially be attributed to the differences in the location of these latrines. It is not the scope of this study, but it will be interesting to investigate how this behaviour changes the overall composition of GINs in alpacas as it might favour certain GIN species over others.…”
Section: Phylogenetic Analysismentioning
confidence: 97%
“…The Blastp search tool revealed that the proteins Fuc25A, Fuc25C, Fuc25D, and Fuc25E are homologous to α-L-fucosidases. The majority of Fuc25A, Fuc25C, and Fuc25D homologs belong to bacteria from the class Clostridia, phylum Firmicutes, which is most abundant in alpaca faeces [26] Fuc25E is homologous to Clostridia or Lentisphaeria bacteria proteins. Analysis of the protein sequences (using the Uniprot peptide search tool) showed that none of the proteins had a secretory signal peptide.…”
Section: Isolation and Bioinformatic Analysis Of α-L-fucosidasesmentioning
confidence: 99%